2021
DOI: 10.1186/s12889-021-10642-x
|View full text |Cite
|
Sign up to set email alerts
|

A bilingual systematic review of South Korean medical tourism: a need to rethink policy and priorities for public health?

Abstract: Background In 2016, the “Act on Support for Overseas Expansion of Healthcare System and Attraction of International Patients” was enacted by the South Korean government in an attempt to accelerate growth of its medical tourism industry. However, only a few years after its implementation, the benefits are not well understood, nor have the positive or negative impacts of expanding Korea’s medical tourism sector been properly evaluated. Objective We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…MT is a forward-looking industry that combines high-quality medical services with tourism and has recently received increasing attention [15]. is study establishes the criteria for evaluating sustainable MT based on relevant academic literature on MT [16][17][18][19][20][21][22][23][24][25][26] and discussion with experts in the tourism and hospitality industries to assess the critical success factors of MT. After several rounds of discussions with the experts, we finally selected 17 criteria that are most relevant to Taiwan's MT.…”
Section: Establishment Of the Mt Assessment Frameworkmentioning
confidence: 99%
See 3 more Smart Citations
“…MT is a forward-looking industry that combines high-quality medical services with tourism and has recently received increasing attention [15]. is study establishes the criteria for evaluating sustainable MT based on relevant academic literature on MT [16][17][18][19][20][21][22][23][24][25][26] and discussion with experts in the tourism and hospitality industries to assess the critical success factors of MT. After several rounds of discussions with the experts, we finally selected 17 criteria that are most relevant to Taiwan's MT.…”
Section: Establishment Of the Mt Assessment Frameworkmentioning
confidence: 99%
“…Millions of travelers worldwide travel for medical purposes each year, and their primary motivations can be broadly categorized as seeking better quality care, lower cost of services, and faster access to medical services, all of which are influenced by macro policy issues [23]. D 3 includes C 31 , C 32 , C 33 , C 34 , and C 35 .…”
Section: Establishment Of the Mt Assessment Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…The host countries consider medical tourism as a source of economic profits [ 1 ]. Previous research in Korea, a patient-accepting country, concluded that the benefits of medical tourism outweigh the negative impacts of universal health coverage and the constriction of medical supply [ 2 ]. Moreover, medical tourism might be a powerful tool for reducing inequalities in healthcare worldwide [ 3 ].…”
Section: Medical Tourism In Cambodiamentioning
confidence: 99%